Integrated Waqf Environment Model (IWEM): Proposal for funding sustainable agriculture through waqf to embrace the Era of Smart Agriculture 5.0 ‎ - Maulida, Syahdatul; Rusydiana, Aam Slamet (Universitas Islam Indonesia, 2025)
IntroductionAlthough global food production has tripled, sustainable agriculture remains threatened by climate change, land degradation, and financial gaps, especially in smallholder communities. This study introduces the Integrated Waqf Environment Model (IWEM) as a waqf-based funding mechanism to support sustainable agriculture. Additionally, sentiment analysis using VADER Python is employed to assess public perceptions of sustainable agriculture.ObjectivesThis research aims to measure public sentiment regarding sustainable agriculture on the Twitter social media platform. Additionally, the study proposes the Integrated Waqf Environment Model (IWEM) for sustainable agriculture funding as a response to the challenges faced in the agricultural sector.MethodThe research methodology involves the extraction and classification of tweet data using the Python library called VADER (Valence Aware Dictionary and Sentiment Reasoner). The study utilizes tweet data posted within the last year. The research findings indicate fluctuations and a decrease in the number of tweets discussing sustainable agriculture. The location with the highest tweet activity related to sustainable agriculture is Brussels, Belgium, with 642 tweets during the observation period.ResultsWord cloud analysis on keywords reveals that, in positive sentiment, terms like